Inclusive, Exclusive, Didactic: Typologies of Islamic Thought on Apostasy in Muhammadiyah - Sholihul Huda; Zuly Qodir; Nafik Muthohirin; Warsidi Warsidi (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2024)
This study explored the typologies of Islamic thought among Muhammadiyah elites in East Java concerning the discourse on apostasy. Responses vary, with the inclusive view treating apostasy as a private matter between the individual and God, a basic human right with no legal consequences, supported by the Qur'an and the 1945 Constitution. The exclusive view, however, sees apostasy as a public offense, where freedom of choice is conditional and legal repercussions are necessary. The didactic perspective understands apostasy as a moral error, best addressed through education and compassionate guidance to encourage a return to Islam. The findings indicate a dominant trend towards inclusive views but reveal inconsistencies, as elites may express inclusive views on religious freedom while adopting exclusive stances on legal aspects of apostasy. Despite these differences, all maintain a didactic approach when dealing with apostasy within families. This study underscored the dynamic nature of Islamic thought in Muhammadiyah, challenging the perception of rigidity and highlighting the influence of diverse sociological and intellectual backgrounds.